PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN MOODLE DI MASA PANDEMI COVID-19 PADA MATA PELAJARAN EKONOMI KELAS X DI SMA 4 MUHAMMADIYAH MAKASSAR - Muhammad Faisal; Muhammad Azis; Nawir Rahman (Media Bina Ilmiah, 2023)
Moodle is an application program that can change learning media into web form. The benefits of using MOODLE online are very important, especially in the current era of the covid-19 pandemic. This research study is about the Development of Interactive Learning Media Using Moodle During the Covid-19 Pandemic in Class X Economics at SMA 4 Muhammadiyah Makassar. This research is a penelitian reserch and development (R&D). Research with 38 students in class X in SMA 4 Muhammadiyah Makassar conducted online. The results of this study indicate that the analysis phase of students requires the development of interactive learning media using Moodle in economics subjects with specialization in the role of economic actors in economic activities, the design of instructional media designs in the form of flowcharts, storyboards, compiling materials, practice questions, quizzes, and compiling media assessment instrumens and student responses. The validation development stage by material experts obtained an average value of 4.61 with the "Very Eligible" category, media expert validation obtained an average value of 4.36 with the "Very Eligible" category, the validation of economic learning practitioners obtained a value of 4, 19 with the "Eligible" category, Implementation Phase (Implementation), at this stage the results obtained showed a positive response with a percentage of 65% for all indicators. From the data obtained, it can be concluded that the delivery of material, questions, and discussions is clear, the media is designed in an attractive manner, the use of media can improve understanding and this media is useful in learning activities. and develop media assessment instrumens and student responses